2018
DOI: 10.1016/j.cgh.2018.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Maintenance Therapy Reduces Rate of Relapse of Pancreaticobiliary Immunoglobulin G4-related Disease

Abstract: In a retrospective study of patients with pancreaticobiliary IgG4-RD, we found rituximab maintenance therapy prolongs remission. Relapses are uncommon among patients receiving maintenance therapy, but maintenance therapy may increase risk of infection. Patients with factors that predict relapse could be candidates for rituximab maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 14 publications
2
44
0
2
Order By: Relevance
“…Rituximab is indicated for patients with recurrent or refractory disease, levels of IgG4 decline rapidly while levels of other IgG subclasses remain stable [17,18]. Unlike IgG4related Sclerosing Cholangitis in which elevated alkaline phosphatase levels are a predictor of relapse after RTX induction therapy in the IgG4-RD, predictive marker isn't known [19,20]; on the other hand the elevation of pretreatment levels of IgG4, immunoglobulin E (IgE) and blood eosinophil concentrations independently predicted future relapses [20]. The objective of the treatment of IgG4-RD is to alleviate symptoms and prevent disease-related complications and irreversible fibrosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab is indicated for patients with recurrent or refractory disease, levels of IgG4 decline rapidly while levels of other IgG subclasses remain stable [17,18]. Unlike IgG4related Sclerosing Cholangitis in which elevated alkaline phosphatase levels are a predictor of relapse after RTX induction therapy in the IgG4-RD, predictive marker isn't known [19,20]; on the other hand the elevation of pretreatment levels of IgG4, immunoglobulin E (IgE) and blood eosinophil concentrations independently predicted future relapses [20]. The objective of the treatment of IgG4-RD is to alleviate symptoms and prevent disease-related complications and irreversible fibrosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Klinisk erfaring tilsier at rituksimab bør tilbys pasienter som ikke tolererer eller ikke oppnår ønsket effekt av prednisolon. Dokumentasjonen for vedlikeholdsbehandling med rituksimab er sparsom (14,15). Patogenesen ved IgG4-relatert sykdom er bare delvis kartlagt, men den gode responsen på rituksimab indikerer at Blymfocytter spiller en sentral rolle.…”
Section: Diskusjonunclassified
“…Among the maintenance regimens, relapses occur in the lowest proportion of patients (w10%) receiving rituximab maintenance (every 6 months). 89 Relapse occurs in 25%-35% of patients who receive lowdose steroid and immunomodulator regimens for maintenance. 90,91 High-dose steroid treatment (40 mg/d for 4 weeks, followed by taper by 5 mg/wk, until patients are off the drugs) is an acceptable regimen for prednisolone 5,92,93 ; rates of response to steroid therapy are 79%-97%, 5,92 whereas rates of relapse to the maintenance therapy are 31%-60%.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…95 A retrospective study showed lower relapse with maintenance rituximab vs observation following induction with rituximab. 96 In this study, 43 patients with pancreaticobiliary IgG4-RD received rituximab, 14 received induction doses only without maintenance therapy, and 29 received induction therapy plus maintenance rituximab. Both groups were followed for similar times after treatment (34 vs 27 months).…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%